2022
DOI: 10.1021/acssuschemeng.1c07741
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Screening of Transition Metal-Embedded Ti2N for High-Efficiency Hydrogen Evolution Reaction

Abstract: Transition metals (TMs) have been widely employed to realize various electrocatalytic applications of pristine materials. Herein, via density functional theory (DFT), the potential for the hydrogen evolution reaction (HER) of all single TMs embedded in Ti 2 N was screened. Our results show that embedded single TMs can tune the hydrogen adsorption with a volcano-like tendency, and Mo-Ti 2 N stands out with an optimal Gibbs free energy (ΔG H ) of −0.097 eV. This can be further improved with an optimal ΔG H close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
4
11
0
Order By: Relevance
“…Additionally, it also surpasses that of the theoretically predicted Mo-Ti 2 N and MoS 2 with edge sites. 53,56 Notably, 1TNi-Mo 2 B exhibits the greatest catalytic activity and is equivalent to the effectiveness of Pd and Pt metal surfaces. 53,56 It is apparent from our work that the 1TNi-Mo 2 B system outperforms even the most common metal catalysts in terms of the HER performance.…”
Section: Her Activity Of Tm-embedded Mbenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it also surpasses that of the theoretically predicted Mo-Ti 2 N and MoS 2 with edge sites. 53,56 Notably, 1TNi-Mo 2 B exhibits the greatest catalytic activity and is equivalent to the effectiveness of Pd and Pt metal surfaces. 53,56 It is apparent from our work that the 1TNi-Mo 2 B system outperforms even the most common metal catalysts in terms of the HER performance.…”
Section: Her Activity Of Tm-embedded Mbenesmentioning
confidence: 99%
“…The adsorption energy of H (Δ E H ) on MBenes is calculated as normalΔ E normalH = E MBenes + normalH E normalM normalB normale normaln normale normals 1 2 E normalH 2 where E MBenes+H , E MBenes , and E H 2 stand for the total energy of Mo 2 B with adsorbed H atom, pristine Mo 2 B, and H 2 molecules in the gas phase. Additionally, the Gibbs free energy (Δ G H ) of these H species is estimated in accordance with the following consideration to estimate the HER activity of MBenes: normalΔ G normalH = normalΔ E normalH + normalΔ ZPE + prefix∫ C normalp .25em normald T T normalΔ S where Δ E H is the H adsorption energy (eq ). The term “ΔZPE” refers to the difference in the zero-point energy between adsorbed H and H 2 in the gas phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Nitrogen‐ and sulfur‐co‐doped Ir [ 58 ] or Ru [ 53 ] in the surface of MXene also exhibited enhanced HER activity, which was attributed to the redistribution of the charge of the active metal atom, improving the adsorption of the intermediate H. [ 39 ] By calculating the formation energy of the anchored TM at the Ti vacancy, Kong et al found that TM tended to embed MXene as a single atom rather than a bulk metal, with a negative adsorption energy ( Figure a,b). [ 73 ] In addition, Mo–Ti 2 N was a potential high‐performance HER catalyst with a hydrogen adsorption–free energy close to that of Pt (Figure 10c). Kuznetsov et al replaced part of Mo in Mo 2 C with Co to form an isolated Co‐based catalyst Mo 2 CT x :Co, similar to bimetallic MXene solid solution, where Mo and Co had the same coordination structure.…”
Section: Applications Of Mxene‐based Sacsmentioning
confidence: 99%
“…Reproduced with permission. [ 73 ] Copyright 2022, American Chemical Society. d) Mo 2 CO 2 :Co model structure used for DFT calculations.…”
Section: Applications Of Mxene‐based Sacsmentioning
confidence: 99%
“…The results show that Mo–Ti 2 N has the best HER Gibbs free energy, and its current exchange density exceeds most of the metal catalysts on the market, which indicates that Mo–Ti 2 N is a feasible HER electrocatalyst. 32 Ren et al The possibility of Mo 2 N as a catalyst for NRR reaction was also studied by theoretical calculation. The results show that the free energy barrier of the potential-determining step of NRR on Mo 2 N is significantly reduced, and Mo 2 N can become a stable and efficient NRR electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%